Level of Household Food Composition Variety: A Case Study in East Java with Shannon Index - Rizkyah, Salsabillah Alif; Rizkiyah, Noor; Rozci, Fatchur (Kadiri University - Faculty of Agriculture, 2025)
Food diversification is one of the efforts to ensure and maintain a balanced availability of food for each staircase. High dependence on rice causes the level of food diversification in East Java to be low. This study aims to take into account the level of household food diversification in East Java. How food diversification is assessed using the Shannon-Wiener Index, with secondary data from BPS East Java in 2022 covering 14 food groups such as rice, tubers, fish, vegetables, and fruits. The results of the study show that the level of food diversification in East Java is in the medium category, with a diversification index of 2.3. Food groups such as fishery products (21%) and processed foods/beverages (19%) dominate public consumption, while oil and coconut (2%) and other consumption (2%) are still relatively low. Geographical, cultural, and urbanization factors influence the dynamics of consumption patterns. However, uneven distribution is one of the obstacles to increasing food diversification, especially for local agricultural products such as vegetables and fruits. The main solutions proposed to increase food diversification include the socialization of diverse food consumption and the empowerment of local food-based MSMEs. These measures are expected to increase food variety and strengthen food security in East Java. In addition, other solutions that can be considered include the development of local flour-based food products, public education about the benefits of local food, the development of agricultural technology, infrastructure improvement, and the use of home yards to grow various types of food crops.